A Case Report Demonstrating How the Clinical Presentation of the Diffuse Sclerosing Variant of Papillary Thyroid Carcinoma Can Mimic Benign Riedel’s Thyroiditis - Jennifer Walsh; Tomas P. Griffin; Carmel B. Ryan; James Fitzgibbon; Patrick Sheahan; Matthew S. Murphy (Case Reports in Endocrinology)
A 44-year-old female presented with a two-month history of a neck mass, sore throat, hoarseness, and intermittent dysphagia. Examination revealed a “woody” hard swelling arising from the right lobe of the thyroid. Clinically this was felt to be classical Riedel’s thyroiditis (RT). Thyroid ultrasound showed a diffusely enlarged, low echogenicity thyroid with a multinodular goitre. An abnormal nodule extending across the isthmus was noted. Following a nondiagnostic fine needle aspiration, an open core biopsy was performed. This showed dense sclerotic fibrosis punctuated by nodular mononuclear inflammatory cells, which obscured follicular epithelial cells consistent with a fibrosing thyroiditis (Riedel’s thyroiditis). A biopsy of pretracheal lymph nodes showed a sclerotic process throughout the lymph nodes and nests of epithelium bands with squamous differentiation obscured by a fibrous process. These findings raised the differential diagnosis of diffuse sclerosing variant of papillary thyroid carcinoma (DSV-PTC) with metastasis to lymph nodes. A total thyroidectomy and pretracheal lymph node dissection were performed. The final histological diagnosis was DSV-PTC. When managing a patient with presumed RT it is important to consider malignancy in the differential. DSV-PTC is one of the more aggressive forms of thyroid cancer but with early diagnosis and appropriate treatment patients may have excellent outcomes.